Implementation of Legal Rules for the Crime of Vehicle Theft(Legal Review of Court Decision Number: 74/Pid.B/2013/PN.Bkn) - Yunara, Edi (Ipso Jure, 2025)
Indonesia has rules for law enforcement to the community. There are various kinds of rules/laws with various motives for criminal acts committed. Among other things, the crime of theft. This research aims to find out the judge's considerations in the application of the law and to find out how the criminal sentence is imposed in the decision. This type of research is normative legal research, using conceptual, legislative, and case approach methods. The results of the study found that in imposing the severity of the sentence that will be imposed by the previous judge, the judge first considers the aggravating matters and those that mitigate the defendant when it is related to the facts that have been revealed in the trial, and the judge uses 2 (two) forms of consideration, juridical and non-juridical. In the decision, the judge sentenced the criminal offense to imprisonment for 10 (ten) months each. So that according to the compiler, in applying an article or law, judges pay more attention to the consequences of the actions of the perpetrators of criminal acts, in order to create a verdict that is as fair as possible for both the defendant, the victim and the community